Formation of creative thinking of schoolchildren in artwork lessons based on information and communication technologies - Капишева, Меруерт (Pedagogy and Psychology, 2020)
This article is devoted to the description of the ways of forming creative thinking among students in artwork classes using information and communication technologies. The purpose of the study is the scientific justification and development of a methodology for the formation of creative thinking of schoolchildren in artwork lessons based on information and communication technologies. The methodological basis of the study was basic research and scientific publications on the problem of the formation of creative thinking using information and communication technologies. The author describes in detail the ways of introducing computer technology into the educational process. The question of how to implement information and communication technologies in the course of a lesson in art work is also being considered. The result of introducing a computer into an artwork lesson is the formation of creative thinking and creative abilities, and the students’ interest in the educational process is growing. The article describes in detail the tasks that will help students form creative thinking.